Planning and conducting research in the Australian ESL classroom - Conlan, Chris (English Australia Pty. Ltd., 2007)
With the ongoing internationalisation of the higher education sector in Australia, ESL programmes have become an increasingly important part of the various pathway programmes being offered by Australian universities. While ESL teaching in universities has, by and large, risen to the task of providing quality preparatory programmes, there are increasing pressures on ESL teachers - for example, the proposed tiering of Australian universities into research-focussed and non-research focussed universities - to produce publishable research. This paper provides a conceptual framework and a practical guide for practising ESL teachers contemplating taking the step into publishing a first research paper.